2018
DOI: 10.1007/s10067-018-4304-y
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile arthritis management in less resourced countries (JAMLess): consensus recommendations from the Cradle of Humankind

Abstract: Juvenile idiopathic arthritis (JIA) is the most prevalent chronic rheumatic disease in children and young people (CYP) and a major cause of pain and disability. The vast majority of the world's children and their families live in less resourced countries (LRCs) and face significant socioeconomic and healthcare challenges. Current recommendations for standards of care and treatment for children with JIA do not consider children living in less resourced countries. In order to develop appropriate recommendations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 72 publications
(72 reference statements)
1
41
0
2
Order By: Relevance
“…Only 4.8% were in remission whereas the median disease duration was 13.8 months (IQR [3.8, 34.5]) which is not in line with international recommendations advocating clinical remission within 6 months following treatment onset [25]. Facing this common problem of shortage of PRst in low and middle countries, JAMLess recommendations advocate that in the absence of PRsts, patients should be assessed by clinicians knowledgeable and skilled in caring for children with rheumatic disorders who, ideally, are affiliated with an established rheumatology clinical network [19]. However Spencer in a commentary has suggested that in countries where PRsts are not available, the help of other specialists is essential and appreciated but this is a stop-gap solution and development of PR in every country is the only acceptable long term solution [42].…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Only 4.8% were in remission whereas the median disease duration was 13.8 months (IQR [3.8, 34.5]) which is not in line with international recommendations advocating clinical remission within 6 months following treatment onset [25]. Facing this common problem of shortage of PRst in low and middle countries, JAMLess recommendations advocate that in the absence of PRsts, patients should be assessed by clinicians knowledgeable and skilled in caring for children with rheumatic disorders who, ideally, are affiliated with an established rheumatology clinical network [19]. However Spencer in a commentary has suggested that in countries where PRsts are not available, the help of other specialists is essential and appreciated but this is a stop-gap solution and development of PR in every country is the only acceptable long term solution [42].…”
Section: Discussionmentioning
confidence: 94%
“…Training programs in pediatric rheumatology which are now available at a few centers in India including this center are essential to provide good care countrywide and reduce patients's journey [22]. Clinicians caring for patients with JIA should be encouraged to organize and participate in relevant educational activities [19]. As advocated in the SHARE survey, educating primary health care providers settled in areas far away from tertiary centers is definitively crucial for improving early referral and also building clinical networks and shared care to facilitate delivery of care closer to home [39].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations